THE ANALYSIS RELATED TO THE FACTORS WHICH AFFECT THE POVERTY LEVELS OF DISTRICTS/CITIES IN JAMBI PROVINCE DURING 2014-2018 - Muhammad Safri (Dinasti Publisher, 2021)
Poverty is an issue faced by nearly all developing countries or third world countries, including Indonesia. Jambi Province is one of the provinces in Indonesia which cannot be separated from poverty. Several efforts have been made by district/city governments in Jambi Province to reduce its levels by implementing the poverty alleviation programs issued by the central government. These implementation of poverty alleviation programs carried out by the district/cities governments in Jambi Province showed there has been reduction over these issues in districts/cities in Jambi Province, but only in a small percentage. The economic growth which tends to increase every year in the districts/cities of Jambi Province has not been followed by a significant reduction in poverty levels. This condition required the districts/cities governments to advance a more comprehensive strategy in carrying out poverty alleviation that takes place in districts/cities of Jambi Province. Therefore, this research aimed to investigate those factors which affected the poverty level in districts/cities of Jambi Province. Data used in this research included panel data, namely the 2013-2018 time series data and the cross section data of 11 districts/cities through the Fixed Effect Model approach. These results showed that economic growth and Human Development Index had a significant negative affect on poverty levels.